Poly-autoimmunity in patients with myasthenia gravis: A single-center experience. (September 2015) - Evoli, Amelia; Caliandro, Pietro; Iorio, Raffaele; Alboini, Paolo E.; Damato, Valentina; LaTorre, Giuseppe; Provenzano, Carlo; Marino, Mirella; Lauriola, Libero; Scuderi, Flavia; Bartoccioni, Emanuela
Abstract We evaluated the co-occurrence of autoimmune diseases (ADs) in a large population of myasthenia gravis (MG) patients from a single center. Our survey included 984 patients, 904 with anti-acetylcholine receptor antibodies and 80 with anti-muscle specific kinase antibodies. The anti-acetylcholine receptor positive population included patients with early-onset (age at onset ≤50 years), late-onset and thymoma-associated disease. Follow-up ranged 2–40 years. Two-hundred and fourteen ADs were diagnosed in 185 patients; 26 of them had two or more ADs in association with MG. Thyroid disorders were the most common and, together with vitiligo and thrombocytopenia, occurred in all disease subsets. Otherwise, there was a broad variability with partial overlap among patient groups. The highest rate of ADs was observed in early-onset patients, while clusters, i.e. 2 or more ADs other than MG in the same individual, were more common among thymoma cases. Thirty-four diseases were diagnosed at the same time, 88 occurred before and 92 after the onset of MG. On multivariate analysis, immunosuppressive treatment was the only independent variable which negatively influenced the risk of developing other ADs in our cohort.